2008
DOI: 10.1189/jlb.1107751
|View full text |Cite
|
Sign up to set email alerts
|

LRG-accelerated differentiation defines unique G-CSFR signaling pathways downstream of PU.1 and C/EBPε that modulate neutrophil activation

Abstract: Expression of leucine-rich alpha-2 glycoprotein (LRG), a member of the leucine-rich repeat family of proteins, was recently shown to be upregulated during neutrophil differentiation. Its precise role in granulopoiesis, however, remains unknown. In this paper, we show that the transcription factors PU.1 and C/EBPε that regulate the expression of multiple myeloid-specific genes also bind to the LRG promoter. We also demonstrate that LRG localizes to the same cytoplasmic compartment as myeloperoxidase and that G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Notably, in our earlier studies in which LRG1 was transfected into murine myeloid cell lines and overexpressed, it was found to localize to the MPO-containing primary granules [17]. In this model system, ectopic expression of LRG1 was driven by a constitutive CMV promoter [23]. It is not surprising then that constitutively expressed LRG1 was found to co-localize with MPO, since LRG1 expression occurred concomitant with MPO expression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, in our earlier studies in which LRG1 was transfected into murine myeloid cell lines and overexpressed, it was found to localize to the MPO-containing primary granules [17]. In this model system, ectopic expression of LRG1 was driven by a constitutive CMV promoter [23]. It is not surprising then that constitutively expressed LRG1 was found to co-localize with MPO, since LRG1 expression occurred concomitant with MPO expression.…”
Section: Discussionmentioning
confidence: 94%
“…Localization of the human gene for LRG1 by our group to a region on chromosome 19 where the genes for multiple neutrophil granule proteins also map prompted us to postulate that LRG1 might be a neutrophil granule protein. Using murine myeloid cell lines transfected with a tagged LRG1 cDNA construct, LRG1 was found to be packaged into the primary granules of differentiating cells [23]. A drawback of these studies was the use of an overexpression system, which can lead to inappropriate targeting of proteins to subcellular compartments that differ from their native counterparts in primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mitochondrial DAMPs including formyl peptides and mitochondrial DNA have been shown to activate human polymorphonuclear neutrophils (PMNs) through the pattern recognition receptors and lead to PMN migration and degranulation in vitro and in vivo (36). Because LRG was shown to be up-regulated during neutrophilic differentiation (8) and be localized in the primary (azurophilic) granule compartment (37), it is possible that LRG functions as one of the pattern recognition receptors of PMN and modulates the neutrophilic function through an innate immune pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Also, LRG has been shown to be associated with neutrophilic differentiation 14,15 and prevention of lymphocyte apoptosis, 17 whereas in hepatoma cell lines, LRG expression has been shown to be associated with increased susceptibility to TGF-induced growth suppression. 18 Some evidence suggests that LRG may be an acute phase protein.…”
Section: Discussionmentioning
confidence: 99%
“…LRG was identified in 1977 as a trace component of human serum, 11 and resolution of the primary structure in 1985 indicated that it existed as a single polypeptide chain of approximately 45 kDa. 12 The precise function of LRG has yet to be defined, but evidence to date suggests that it is associated with inflammatory responses and neutrophilic differentiation [13][14][15][16][17] as well as cellular responses to the profibrotic cytokine transforming growth factor (TGF)-␤. 18,19 A growing body of data suggests that myocardial fibrosis is a central abnormality in the pathogenesis of HHD, DD, and the development of HF.…”
mentioning
confidence: 99%